Feminist approaches to promoting researcher well-being through collective and organizational care - Carlson, Catherine; Namakula, Sylvia; Nabachwa, Agnes Grace; Gevers, Anik; Morgan-Babikov, Kelsey; Giorgio Cosenzo, Luciana; Ticozzi, Melissa; Namy, Sophie (Frontiers in Sociology, 2024)
Researchers working in the field of violence against women and children are often tasked with listening to highly distressing personal accounts of violence and subsequent trauma. Without proper attention and mitigation strategies, this exposure can lead to vicarious trauma and related symptoms with significant impact on researchers’ well-being. As women are often leading and carrying out violence research, they also experience a disproportionate burden of risk of vicarious trauma symptoms. This case study highlights seven collective care strategies for research implemented by Healing and Resilience after Trauma (HaRT), a feminist organization dedicated to holistic healing among survivors of human trafficking and gender-based violence, whose team is entirely composed of women. Further, it explores how creating and integrating collective care into research protocols can help prevent vicarious trauma and enhance researchers’ emotional well-being as well as positively influence research quality. Qualitative data from researchers involved in the study on these strategies and how they affected their well-being are included. The piece concludes by discussing potential recommendations for other research teams and organizations seeking to mitigate the risk of vicarious trauma.